Orbital trauma with a large wooden foreign body: a case report - Chromińska, Karolina; Bąk, Tomasz Krzysztof; Wojciechowicz, Jolanta; Gawęda, Anna; Tomaszewski, Tomasz (Journal of Education, Health and Sport, 2018)
Introduction: Injuries caused by a foreign bodies in the craniofacial region constitute a significant percentage of accidents during the work. The most serious problem is to determine the exact location and extent of damage caused by a foreign body. The aim of work is to present a scheme of conduct in case of a foreign body inside the eye socket.Matherials and methods: Describes a case of a patient with an injury caused by a wooden foreign body. The circumstances of occurrence, ophthalmic and surgical actions taken in order to remove it were included. A lot of attention has been paid to prevention of intraocular infections.Results: Patient did not find both post-traumatic and postoperative ophthalmic nerve injuries.Summary: The most important for healing process is exact removal of the foreign body and prophylaxis of infections. In addition to treatment, it is important to educate the patient in the prevention of this type of injury.